ANALISIS PENGARUH INFLASI, SUKU BUNGA DAN PRODUK DOMESTIK BRUTO TERHADAP PROFITABILITAS - Firna Widiyanti (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
Purpose of this research was to find effect of inflation, interest rates and gross domestic product on profitability. Data was financial report published by Bank Mandiri. Population of this research was 10. Multiple regression analysis with the SPSS 24 program was used in the research for data analysis. Result of the research showed t test that partially the inflation variable had no significant effect on profitability. The interest rate and the gross domestic product variable has no significant effect on profitability. The f test result of the research showed that simultaneously inflation, interest rates and gross domestic product variables have a significant effect on profitability.